Vietnamese Consumers' Willingness to Pay for Safe Pork in Hanoi. Issue 4 (2nd October 2019) - Thi Nguyen, Hao; Nguyen, Quoc Chinh; Kabango, Amon Ngasha; Pham, Tien Dat
Abstract: Food safety is one of the main concerns and the biggest challenge for consumers due to its direct influence on human health. In order to deal with unsafe food situation, the demand for food hygiene has increased in recent years as well as the consequent increase in price accepted by consumers. This study aimed to estimate consumers' willingness to pay (WTP) and to examine the determining factors influencing their WTP for safe pork using double-bounded dichotomous choice contingent valuation method (DBDC CVM). The data were collected from a survey with a sample size of 134 respondents in Hanoi, Vietnam using two sets of questionnaires on the consumption of rib and shoulder of pork. The results revealed that the percentages of the consumers willing to pay a premium for more hygiene shoulder and rib of pork were 81.75% and 73.01%, respectively. The mean WTP was 129, 000 VND (US$6.07) for both safe shoulder and rib, 48.7% and 37.8% higher than the regular market price, respectively. The results showed that consumers' awareness of the risk of unhealthy pork, household income and expenditure were the positive determinants to WTP; meanwhile, the amount of pork consumption per month negatively affected the willingness to pay more for shoulder and rib of pork.